2015
DOI: 10.1159/000441006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propofol on the Dynamic Properties of Sensory Information Processing in the Mouse Cerebellar Cortical Molecular Layer in vivo

Abstract: Propofol is a global central nervous system depressant that affects information processing in the central nervous system. However, the effects of propofol on sensory information processing in the cerebellar cortical molecular layer are unknown. In this study, we examined the effects of propofol on the dynamics of sensory stimulation-evoked responses in the cerebellar molecular layer in urethane-anesthetized mice, using electrophysiological and pharmacological methods. Our results showed that cerebellar surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Additionally, propofol has been implicated in causing movement disorders since 30 years ago, which strongly suggests that propofol may damage the cerebellum (Dingwall, 1987 ; Zabani and Vaghadia, 1996 ; Bendiksen and Larsen, 1998 ; Brooks, 2008 ). Recent studies have also indicated that propofol depressed Purkinje cell activity and affected the cerebellum circuitry (Jin R. et al, 2015 ; Jin W. Z. et al, 2015 ; Lee K. Y. et al, 2015 ). However, little is known regarding the impact of propofol exposure on the development of the cerebellar neuronal population.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, propofol has been implicated in causing movement disorders since 30 years ago, which strongly suggests that propofol may damage the cerebellum (Dingwall, 1987 ; Zabani and Vaghadia, 1996 ; Bendiksen and Larsen, 1998 ; Brooks, 2008 ). Recent studies have also indicated that propofol depressed Purkinje cell activity and affected the cerebellum circuitry (Jin R. et al, 2015 ; Jin W. Z. et al, 2015 ; Lee K. Y. et al, 2015 ). However, little is known regarding the impact of propofol exposure on the development of the cerebellar neuronal population.…”
Section: Introductionmentioning
confidence: 99%